IMPLEMENTASI AUDIT SEKTOR PUBLIK DALAM PENCEGAHAN FRAUD PADA INSPEKTORAT KOTA BIMA - GALANG AMBARWATI, SEPTYANTY Galang (Jurnal Akuntansi AKUNESA, 2013)
Increasing levels of fraud in Bima is significantly each year, then the role of public sectoraudit in fraud should be increased in tackling fraud prevention, So this study aims to determinethe effect of the implementation of public sector audit in preventing fraud in the CityInspectorate Bima. The method used in this research is Simple linear regression analysis, byspreading questionnaire on all employees of the secretariat on the Bima city inspectorate asmany as 20 samples. The results of this study indicate that the public sector audit influence theprevention of fraud.Keyword : Public Sector Audit, Fraud, Prevention of Fraud.